2019
DOI: 10.1186/s41240-019-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Garcinia kola seeds supplemented diet on growth performance and gonadal development of Oreochromis niloticus juveniles breed in ponds

Abstract: Background: Despite the favorable geo-climatic potential of Cameroon, the national production of tilapia remains low due to poor tilapia growth reported by fish farmers. One of the underlying reasons is the early female maturation at a very small size and precocious breeding in earthen ponds, resulting in overpopulation which leads to stunted growth and therefore to the production of unmarketable fish size. Studies have shown that dietary supplementation of G. kola enhanced growth in young Clarias gariepinus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The improved final body weight and better conversion of feed-to-meat ratio recorded in rabbits fed dietary 1.5% GKSM may be due to GKSM increasing nutrient absorption from the gastrointestinal tract [50] at this level (1.5% GKSM). This result agrees with the findings of Nyadjeu et al [28], who reported that dietary GKSM significantly enhanced growth response in juvenile fish.…”
Section: Growth Performance Indicessupporting
confidence: 93%
See 2 more Smart Citations
“…The improved final body weight and better conversion of feed-to-meat ratio recorded in rabbits fed dietary 1.5% GKSM may be due to GKSM increasing nutrient absorption from the gastrointestinal tract [50] at this level (1.5% GKSM). This result agrees with the findings of Nyadjeu et al [28], who reported that dietary GKSM significantly enhanced growth response in juvenile fish.…”
Section: Growth Performance Indicessupporting
confidence: 93%
“…These bioactive compounds inherent in the medicinal plants give them the ability to decrease the population of growth-depressing gut microbial metabolites, thereby increasing the available nutrients for the animal's utilization [48]. Flavonoids are non-nutritive plant components found commonly in different plant parts, such as flowers, barks, fruits, nuts, and seeds [28]. There are reports that GKSM promotes growth in animals due to its bioflavonoid contents [23].…”
Section: Growth Performance Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockage of estrogen synthesis causes anti‐fertility effects, which can be harnessed to control animal reproduction (Abu, Amuta, Buba, & Inusa, 2013; Akinloye, Igharna, Olaniyi, Alaka, & Oke, 1999). In aquaculture, the inclusion of 1, 3, and 6% of bitter kola seed powder in the diet of female Nile tilapia for 70 days diets mixed resulted in the impairment of gonadal development (Nyadjeu, Angoun, Ndasi, & Tabi‐Tomedi, 2019). Besides, significant reduction (83.45%) in the number of eggs spawned by Nile tilapia, maintained on a diet constituting of 6% bitter kola seed powder for 44 days (Sulem‐Yong et al, 2018) was linked to the presence of flavanoids.…”
Section: Plant Extracts Used In the Control Of Tilapia Reproductionmentioning
confidence: 99%